TRADISI MEULEUM HARUPAT DALAM PERNIKAHAN ADAT SUNDA PERSPEKTIF URF - Mutammimah, Bidayatul; Suwandi, Suwandi (Al-Syakhsiyyah: Journal of Law & Family Studies, 2023)
The Meuleum Harupat tradition is a tradition that belongs to the authentic urf. It is binding for the bride and groom who hold their wedding ceremony with a traditional Sundanese wedding. The purpose of writing this article is to describe the Meuleum Harupat tradition in Sundanese traditional weddings from the urf perspective. The research method of this article uses a qualitative descriptive approach that aims to explore the Meuleum Harupat tradition and study it with urf. There are three research results in this article: [1] the Meuleum Harupat tradition consists of processions and contains meaning containing marriage advice. [2] urf can be a benchmark for whether or not a tradition is recognized as a legal basis, as long as it does not contradict sharia law or Islamic religious values. [3] the Meuleum Harupat tradition is included in the urf shahih which deserves to be recognized as a tradition that exists in traditional Sundanese weddings so that this tradition is binding and must be carried out for both bride and groom who decided to hold their wedding with a traditional Sundanese wedding.